Tracing Commoner Health Problems among Tribal School Children of the Dang District of Gujarat - Chhaya, Jatin; Bhabhor, Hitesh; Vyas, Shailee; Moitra, Mohua; Kosambiya, Jayesh K (National Journal of Community Medicine, 2018)
Background: Development, food security, safe housing and sanita- tion being the rights of every citizen. Health is inseparable compo- nent of these essentials of living. Tribal population is poorest and experience extreme levels of health deprivation and that’s why they lag behind state as well as national average on several health indicators. Tribal children being most vulnerable, this study is planned to know morbidity profile of the tribal children living in residential hostel in Dang district. Methodology: Community Medicine Department of Government Medical College, Surat conducted general health check-up camp for the benefit of tribal students. Result: One hundred and seventeen students from 5 tribal residen- tial hostels were beneficiaries of this camp. Dental caries, Ear wax and discharge, passing worms in stool, refractive errors and skin infection were some common problems identified and treated in the camp. Conclusion: Personal hygiene and oral health is more compromis- ing factor that becomes hurdle for their overall development. Pe- riodical health check-up and health education is most needed es- pecially for tribal children.